PARADIGM OF DEATH PENALTY (COMPARATIVE STUDY IN INDONESIA, SAUDI ARABIA AND CHINA) - Tedy Nopriandi; Risky Fany Ardhiansyah (Faculty of Law Universitas Lampung, 2020)
The death penalty is one of old criminal type as the age of human life, and the most controversial crime in of all criminal systems, both in countries that adhere to the Common Law System and in countries that embrace Civil Law, Islamic Law and Socialist Law. There are two main thoughts about the death penalty, namely: first, those who want to keep it based on the force provisions, and second are those who wish to the abolition as a whole. Indonesia includes a country that still maintains capital punishment in a positive legal system. This paper aims to resolve problems of the death penalty concept concerning the controversy purpose of the death penalty and to analyze the regulations, procedures and philosophies regarding the death penalty in Indonesia, Saudi Arabia and China. This paper uses normative juridical research and the methods based on the doctrine and developed by the author. The approach used the legal approach, historical approach and comparative approach, then analyzed by the customary method. The result of the study shows that the death penalty can be seen from the philosophical aspects of Indonesian criminal law, as well as the philosophical aspects of Islamic and Chinese criminal law. So that everything can not be separated from the essential legal objectives, namely for the creation of justice. Death penalty in Islamic law turns out the concept of restorative justice specifically for the crime of deliberate killing (al-qatl al-'amd), which the execution highly depends on the victim’s family. The victim’s family, in this case, has the right to choose whether qisas (death penalty) or their apologize for the murder suspect, and diyat payment. While China in the implementation of death penalty applies the concept of rehabilitation, which in the execution of the death penalty is called a death penalty delay for two years and in its implementation, the defendant is given a job and control them. Whereas in Indonesia, capital punishment is a specific criminal offence and threatened with alternatives and is still a draft Criminal Code.